K+12-6k=-27k

Simple and best practice solution for K+12-6k=-27k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for K+12-6k=-27k equation:


Simplifying
K + 12 + -6k = -27k

Reorder the terms:
12 + K + -6k = -27k

Solving
12 + K + -6k = -27k

Solving for variable 'K'.

Move all terms containing K to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + K + -12 + -6k = -12 + -27k

Reorder the terms:
12 + -12 + K + -6k = -12 + -27k

Combine like terms: 12 + -12 = 0
0 + K + -6k = -12 + -27k
K + -6k = -12 + -27k

Add '6k' to each side of the equation.
K + -6k + 6k = -12 + -27k + 6k

Combine like terms: -6k + 6k = 0
K + 0 = -12 + -27k + 6k
K = -12 + -27k + 6k

Combine like terms: -27k + 6k = -21k
K = -12 + -21k

Simplifying
K = -12 + -21k

See similar equations:

| 2x+7=2x-67 | | 9x+17+3x+19=180 | | 8x-8=-8x+24 | | -3(x-5)=3(5-x) | | 2x+7=1x+9 | | 10/m=5/11 | | 32=4+6x | | 4j+j= | | x-2=2x-91 | | N-5+4=8 | | 2x+2=11-x | | 1/4/12=n | | 2(c+7.2)=3.2 | | 18x-4=58+10x-8 | | -5+4y= | | x+78=2x-14 | | 2z=-1/2 | | -2x(5x+3)= | | 9*n+6=18 | | 5+(-11)+14= | | 2x=-(3y+1) | | (H/6)-2=15 | | 7(7x+4)+1=78 | | 3r+2=2r+2 | | 6x-79=x-4 | | 4x+2=12x+6 | | 120=21x-6 | | 2x+24=3x+24-1 | | 5/7-13/24= | | 8(5x+9)= | | -b+4y= | | 2x+1=-3y |

Equations solver categories